Predicting Physical Activity‐Related Outcomes in Overweight and Obese Adults: A Health Action Process Approach. Issue 1 (March 2016) - Hattar, Anne; Pal, Sebely; Hagger, Martin S.
Abstract : Background: We tested the adequacy of a model based on the Health Action Process Approach (HAPA) in predicting changes in psychological, body composition, and cardiovascular risk outcomes with respect to physical activity participation in overweight and obese adults. Methods: Measures of HAPA constructs (action and maintenance self‐efficacy, outcome expectancies, action planning, risk perceptions, intentions, behaviour), psychological outcomes (quality of life, depression, anxiety, stress symptoms), body composition variables (body weight, body fat mass), cardiovascular risk measures (total cholesterol, low density lipoprotein), and self‐reported physical activity behaviour were administered to participants ( N = 74) at baseline, and 6 and 12 weeks later. Results: Data were analysed using variance‐based structural equation modelling with residualised change scores for HAPA variables. The model revealed effects of action self‐efficacy and outcome expectancies on physical activity intentions, action self‐efficacy on maintenance self‐efficacy, and maintenance self‐efficacy and intentions on action planning. Intention predicted psychological and body composition outcomes indirectly through physical activity behaviour. Action planning was a direct predictor of psychological, cardiovascular, and body composition outcomes. Conclusions: Data supported HAPA hypotheses in relation to intentions and behaviour, but not the role of action planning as a mediator of the intention–behaviour relationship. Action planning predicted outcomes independent of intentions and behaviour.